2014
DOI: 10.1002/adfm.201304060
|View full text |Cite
|
Sign up to set email alerts
|

The Size Dependence of Hydrogen Mobility and Sorption Kinetics for Carbon‐Supported MgH2 Particles

Abstract: MgH 2 is a promising material for reversible solid-state hydrogen storage. It is known that particle size can have a strong impact on hydrogen dynamics and sorption characteristics, but more detailed insight has been hampered by the great challenge to prepare small and well-defi ned particles and study their hydrogen storage properties upon cycling. The preparation of MgH 2 nanoparticles supported on high surface area carbon aerogels with pore sizes varying from 6-20 nm is reported. Two distinctly different Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…Obviously, ball-milling can effectively decrease the size of powders and create more fresh surfaces. Previous reports had demonstrated that the reaction kinetics of MgH 2 was enhanced with its decreasing particle size, caused by a larger surface to volume ratio and decreased diffusion distance for hydrogen [19]. Due to the agglomeration, the pure MgH 2 sample had some visible large clusters existed.…”
Section: Structure and Catalytic Mechanismmentioning
confidence: 90%
“…Obviously, ball-milling can effectively decrease the size of powders and create more fresh surfaces. Previous reports had demonstrated that the reaction kinetics of MgH 2 was enhanced with its decreasing particle size, caused by a larger surface to volume ratio and decreased diffusion distance for hydrogen [19]. Due to the agglomeration, the pure MgH 2 sample had some visible large clusters existed.…”
Section: Structure and Catalytic Mechanismmentioning
confidence: 90%
“…The first systematic study of the kinetics of hydrogen sorption as a function of particle size was conducted by Au et al [67], using 6-20 nm MgH 2 particles in carbon aerogels. As shown in Fig.…”
Section: Nanoconfinementmentioning
confidence: 99%
“…(Wilcoxon and Abrams, 2006;Roesler and Fischer, 2015). Another interesting technique is the melt infiltration of low temperature melting metals, such as Mg, into different porous carbon hosts (de Jongh and Eggenhuisen, 2013;Au et al, 2014). For both synthetic method many experimental parameters are plying a crucial role to ensure the stability toward coalescence and the high dispersion of such nanoparticles on the support: the porosity/surface chemistry of the support, the nature of metal precursor, the metal loading, and the synthesis conditions: temperature, reducing agent, etc.…”
Section: Synthesismentioning
confidence: 99%